Selective Fischer-Tropsch synthesis for gasoline production over Y, Ce, or La-modified Co/H-β. (15th February 2020) - Zhuo, Yexin; Zhu, Lingjun; Liang, Jiacheng; Wang, Shurong
Graphical abstract: Abstract: Selective Fischer-Tropsch synthesis has been carried out over a series of Co/H-β catalysts to investigate the influence of rare-earth metal ions promotion on the synthesis of gasoline-range hydrocarbons (GRHs, C5 –C12 hydrocarbons). H-β zeolite was doped with rare-earth metal ions, specifically Y 3+, Ce 3+ and La 3+, by an ion-exchange method. The resulting catalysts were characterized by different methods, namely ICP-OES, BET, XRD, TEM, STEM-EDS, H2 -TPR, NH3 -TPD, CO-TPD and TG. It was found that the addition of Y 3+ improved the dispersion of active components over the Co/H-β catalyst, while doping with Ce 3+, having the ability to change its valence state as well as the number of oxygen vacancies of the support, enhanced the catalyst reducibility. However, the addition of La 3+ tended to cause agglomeration of the active particles due to its large ionic radius. Performance tests showed that the Co/Y-β and Co/Ce-β catalysts achieved higher CO conversions. Due to the moderate acidity and the enhanced CO-metal bonding, the Co/Y-β catalyst exhibited optimal GRHs selectivity of 49% with a yield of 41.4% at 260 °C, 2 MPa, H2 /CO = 2, and 1064 h −1 . More light hydrocarbons were produced after ion-exchange with La 3+ because new strongly acidic sites were formed in the zeolite, leading to low GRHs production.